ANALISIS QOS JARINGAN PEMERINTAH MENGGUNAKAN TEKNIK DEEP PACKET INSPECTION - Julius Samosir; Tomi Loveri; Anton Zulkarnain Sianipar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Digital transformation in the government sector positions computer networks as critical infrastructure to support administrative processes, cross-unit coordination, and online public services. The high dependency on digital services requires network performance that is not only technically reliable but also stable from the user’s perspective. This study aims to analyze the performance of a government network based on Quality of Service (QoS) parameters, including throughput, delay, jitter, and packet loss, using Deep Packet Inspection (DPI) techniques. Measurements were conducted over five working days using Wireshark to capture and analyze network traffic in detail. In addition to technical measurements, user experience validation was performed using the Mean Opinion Score (MOS) method through structured interviews. The results show that delay and packet loss values fall into the very good category according to ITU-T standards, while the average jitter value of 206.0 ms is classified as poor. The study reveals an interesting anomaly in which the physical infrastructure demonstrates excellent delay and packet loss performance, yet high traffic instability (jitter) significantly degrades user experience quality. This condition is consistent with MOS results, which indicate decreased user satisfaction, particularly during online meetings. These findings suggest that the primary issue lies not in physical infrastructure but in the absence of traffic management and prioritization. The study recommends implementing priority-based Quality of Service policies to enhance network stability and support digital bureaucracy optimization.